2023
DOI: 10.3390/ijerph20021395
|View full text |Cite
|
Sign up to set email alerts
|

Can Regional Integration Reduce Urban Carbon Emission? An Empirical Study Based on the Yangtze River Delta, China

Abstract: Regional integration can significantly affect carbon emissions, but scholars have paid more attention to the impact of integration level, ignoring the importance of regional integration expansion. This study attempts to demonstrate whether, in the process of promoting carbon peak and carbon neutrality in China, the transformation of the administrative region’s economy into an integrated economy based on urban agglomeration regional integration expansion affects urban carbon emissions. This study considers the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Another study treats the expansion of the Yangtze River Delta Urban Economic Coordination Council as a quasi-natural experiment, using the same period data as ours. It also concluded that regional integration enlargement of the YRD reduced carbon emissions [63]. However, our study does not focus on regional integration enlargement but rather emphasizes the impact of regional integration policies on construction land and their subsequent effect on carbon emissions.…”
Section: Discussionmentioning
confidence: 83%
“…Another study treats the expansion of the Yangtze River Delta Urban Economic Coordination Council as a quasi-natural experiment, using the same period data as ours. It also concluded that regional integration enlargement of the YRD reduced carbon emissions [63]. However, our study does not focus on regional integration enlargement but rather emphasizes the impact of regional integration policies on construction land and their subsequent effect on carbon emissions.…”
Section: Discussionmentioning
confidence: 83%
“…To better integrate economic development and environmental protection, we use carbon emission intensity to replace GTFP to measure the level of urban green development and calculate the carbon emission intensity of urban areas using the real GDP adjusted for price changes based on the 2003 benchmark year [ 64 ].…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…The establishment of the UECC in the Yangtze River Delta is a pivotal policy in the implementation of China's regional integration strategy, while the difference-in-differences (DID) model serves as a prevalent approach in the field of policy impact evaluation [25,81]. Therefore, to investigate the potential for regional integration in achieving a win-win situation for economic growth and environmental protection, we employed a DID model to assess the impact of the expansion of the UECC on GTFP:…”
Section: Identifying Whether Regional Integration Can Achieve a Win-w...mentioning
confidence: 99%
“…Prior to employing the DID method for policy evaluation, it is imperative to satisfy the assumption of a common trend between the treatment and control groups, ensuring consistent changes in both groups before policy implementation. In this study, we adopt the event study approach to conduct a parallel trend analysis, verifying the dynamic impact of GTFP during the observed sample period [25,81]. Figure 5 demonstrates the GTFP pattern before and after introducing the expansion of the UECC.…”
Section: Promoting Green Transformationmentioning
confidence: 99%